An Optimization Strategy for Intra-day Demand Response Based on Security Constraints. Issue 1 (February 2021) - Sun, Ziru; Chen, Minyu; Ai, Qian; Zhao, Long; Liu, Xiaoming; Sun, Donglei
Abstract: Demand response(DR) has become an effective means to deal with renewable energy integration and load fluctuations in the power system. This article first analyzes the classification and characteristics of controllable resources used in DR. Secondly, taking into consideration the transferable load, interruptible load and the energy storage system in DR, an intra-day scheduling model is then established based on safety constraints. Finally, a case is studied to analyze the role of DR in improving system safety and reducing operating costs. Results show the effectiveness of this model.